Thermal insulation coating composition, thermal insulation coating and preparation method thereof, and lithium ion battery

By coating a heat-insulating coating composition containing modified hollow ceramic material, modified mica and modified inorganic whisker material on the battery cell shell of the lithium-ion battery, the shell melting and rupture of the lithium-ion battery in the case of thermal runaway is solved, and the safety and thermal safety performance of the battery are significantly improved.

CN119775809APending Publication Date: 2025-04-08SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411996265.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Lithium-ion batteries may face the risk of thermal runaway in extreme cases, causing the battery cell shell to melt and rupture, affecting the safety and performance of the battery.

Method used

A heat-insulating coating composition is developed, including modified hollow ceramic materials, modified mica and modified inorganic whisker materials, to form a highly efficient heat-insulating coating by mixing with alkaline silica sols, silane coupling agents and silicate compounds, and coated on the surface of the battery cell housing to enhance its thermal insulation and mechanical strength.

Benefits of technology

It improves the safety of the battery and the thermal runaway protection effect, delays the increase in the surface temperature of the shell, suppresses the shell temperature below the metal softening point, thereby improving the impact strength of the shell, preventing the explosion problem caused by melting the shell under high temperature conditions, and improving the thermal safety performance of the battery module and battery pack.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224573270000111
    Figure BDA0005224573270000111
  • Figure BDA0005224573270000112
    Figure BDA0005224573270000112
  • Figure BDA0005224573270000121
    Figure BDA0005224573270000121
Patent Text Reader

Abstract

The present invention provides a thermal insulation coating composition, a thermal insulation coating and a preparation method thereof, and a lithium-ion battery. The thermal insulation coating composition comprises: component A and component B, component A comprises a modified hollow ceramic material, modified mica and a modified inorganic whisker material; wherein the modified hollow ceramic material is a hydroxyl-modified hollow ceramic material, the modified mica is a hydroxyl-modified mica, and the modified inorganic whisker material is a hydroxyl-modified inorganic whisker material; component B comprises an acidic catalyst, a solvent, an alkaline silica sol, a silane coupling agent and a silicate compound. The introduction of the above-mentioned component A in the present application can improve the thermal insulation performance and mechanical strength of the thermal insulation coating prepared therefrom, and can also improve its adhesion on the surface of the battery cell shell and its resistance to electrolyte corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coating preparation, and in particular to a thermal insulation coating composition, a thermal insulation coating and a preparation method thereof, and a lithium ion battery. Background Art

[0002] As the global demand for renewable energy and electric vehicles surges, the safety and thermal performance of lithium-ion batteries, as a core energy storage technology, have received unprecedented attention. In the construction of lithium-ion batteries, square-shell cells have become the first choice in electric vehicles, energy storage systems and other fields due to their high energy density, good thermal management and easy large-scale production. However, lithium-ion batteries may face the risk of thermal runaway in extreme cases.

[0003] During thermal runaway, the rapid accumulation of heat inside the battery causes the temperature of the battery cell shell (usually aluminum-manganese alloy) to rise sharply, exceeding its melting point (about 600-700°C). The softening and melting of the aluminum-manganese alloy shell may not only cause the shell structure to fail quickly and rupture, but also cause the high-temperature and high-pressure gas generated inside the battery to escape disorderly, and the heat inside the battery to diffuse disorderly in the battery pack or module, seriously affecting the overall safety and performance.

[0004] At present, the thermal runaway protection strategy commonly adopted by the industry is to design an explosion-proof valve, which opens when the battery temperature reaches a certain threshold to control the pressure and guide the hot air flow to be discharged from the explosion-proof valve in a directional manner, thereby achieving the thermal runaway protection effect. However, when the shell temperature rises too quickly to above the melting point, the explosion-proof valve may not be able to respond in time before the shell ruptures, resulting in disordered release of hot air flow and chemicals, thereby reducing the thermal runaway protection effect.

[0005] Therefore, researching and developing a material that can effectively enhance the strength of the battery cell shell and provide additional thermal insulation protection at high temperatures has become an important research direction for improving the overall thermal safety of lithium-ion batteries. This requires not only that the material has excellent thermal insulation properties and chemical stability, and can withstand long-term erosion by the electrolyte inside the battery, but also that it has good bonding strength with the shell to ensure stability during battery use. Summary of the invention

[0006] The main purpose of the present invention is to provide a thermal insulation coating composition, a thermal insulation coating and a preparation method thereof and a lithium ion battery, so as to solve the problem in the prior art that the battery cell shell is prone to melting, burning through and rupture after thermal runaway occurs in the battery.

[0007] In order to achieve the above-mentioned purpose, the present invention provides a thermal insulation coating composition on the one hand, which comprises: component A and component B, wherein component A comprises modified hollow ceramic material, modified mica and modified inorganic whisker material; wherein the modified hollow ceramic material is a hydroxyl-modified hollow ceramic material, the modified mica is a hydroxyl-modified mica, and the modified inorganic whisker material is a hydroxyl-modified inorganic whisker material; component B comprises an acidic catalyst, a solvent, an alkaline silica sol, a silane coupling agent and a silicate compound.

[0008] Furthermore, in parts by weight, component A includes 10 to 21 parts of modified hollow ceramic material, 5 to 10 parts of modified mica, and 5 to 10 parts of modified inorganic whisker material; component B includes 0.1 to 3 parts of acidic catalyst, 1 to 6 parts of solvent, 20 to 40 parts of alkaline silica sol, 20 to 40 parts of silane coupling agent and 5 to 10 parts of silicate compound.

[0009] Furthermore, in parts by weight, component A includes 15 to 21 parts of modified hollow ceramic material, 5 to 8 parts of modified mica, and 5 to 8 parts of modified inorganic whisker material, and component B includes 1.2 to 1.6 parts of acidic catalyst, 1.5 to 2.5 parts of solvent, 25 to 35 parts of alkaline silica sol, 25 to 30 parts of silane coupling agent and 6 to 8 parts of silicate compound.

[0010] Furthermore, the weight ratio of component A to component B is (25-35):(65-75).

[0011] Furthermore, the weight ratio of component A to component B is (30-32):(67-70).

[0012] Furthermore, component A includes at least two hydroxyl-modified hollow ceramic materials with average particle sizes of 5 to 10 μm and 15 to 50 μm, respectively.

[0013] Furthermore, the amount of the hollow ceramic material with an average particle size of 15 to 50 μm is greater than the amount of the hollow ceramic material with an average particle size of 5 to 10 μm; more preferably, the weight ratio of the two is (2 to 3):1.

[0014] Furthermore, the average particle size of the mica is 10 to 15 μm.

[0015] Furthermore, the mica is selected from one or more of the group consisting of phlogopite, sericite and fluorophlogopite.

[0016] Furthermore, the inorganic whisker material is selected from potassium titanate whiskers and / or calcium sulfate whiskers.

[0017] Furthermore, the aspect ratio of the potassium titanate whisker is (10-15):1.

[0018] Furthermore, the aspect ratio of the calcium sulfate whisker is (10-15):1.

[0019] Furthermore, the inorganic whisker material is a combination of potassium titanate whiskers and calcium sulfate whiskers, and the weight ratio of the two is (1-2):1.

[0020] Furthermore, the acidic catalyst is selected from p-toluenesulfonic acid, hydrochloric acid and glacial acetic acid; preferably, the weight ratio of p-toluenesulfonic acid, hydrochloric acid and glacial acetic acid is (0.1-0.5):(0.1-0.5):(0.5-1.5); preferably, the mass concentration of hydrochloric acid is 3.65-7.3 g / L.

[0021] Further, the solvent is selected from one or more of the group consisting of isopropyl alcohol, acetone and water.

[0022] Furthermore, the solid content of the alkaline silica sol is 10 to 35 wt %.

[0023] Further, the silane coupling agent is selected from one or more of the group consisting of methyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane and triethoxyvinylsilane.

[0024] Furthermore, the silicate compound is selected from tetraethyl orthosilicate.

[0025] In order to achieve the above-mentioned purpose, another aspect of the present invention also provides a method for preparing a thermal insulation coating, which comprises: step S1, hydroxylating and modifying a hollow ceramic material, mica and an inorganic whisker material to obtain a modified hollow ceramic material, a modified mica and a modified inorganic whisker material; step S2, mixing an acidic catalyst, a solvent and an alkaline silica sol to obtain a mixed system; step S3, mixing the modified hollow ceramic material, the modified mica, the modified inorganic whisker material and the mixed system with a silane coupling agent and a silicate compound to obtain a thermal insulation coating; step S4, coating the thermal insulation coating on the surface of a battery cell shell, and obtaining a shell containing a thermal insulation coating after curing; the modified hollow ceramic material, the modified mica, the modified inorganic whisker material, the acidic catalyst, the solvent, the alkaline silica sol, the silane coupling agent and the silicate compound have the same definitions as in the above text.

[0026] Furthermore, step S1 includes: mixing and reacting the hollow ceramic material, mica and inorganic whisker material with hydrogen peroxide to obtain a product system containing a modified product; mixing the modified product with water to obtain an aqueous dispersion of the modified product, and spray-drying the aqueous dispersion to obtain a modified hollow ceramic material, modified mica and modified inorganic whisker material; the mixing and reacting process is preferably carried out under stirring conditions, preferably with a stirring rate of 200 to 500 rpm and a stirring temperature of 80 to 120°C.

[0027] Furthermore, the ratio of the sum of the weights of the hollow ceramic material, mica and inorganic whisker material to the volume of hydrogen peroxide is (20-40) g:(20-50) L; preferably, the mass concentration of hydrogen peroxide in hydrogen peroxide is 300-500 g / L.

[0028] Furthermore, the spray drying temperature is 100-110° C., the time is 0.5-2 h, and the pressure is 0.6-1.0 MPa.

[0029] Further, step S2 comprises: mixing an acidic catalyst with a solvent to obtain an acidic catalyst dispersion, and dropping the acidic catalyst dispersion into an alkaline silica sol under stirring conditions to obtain a mixed system, wherein the pH of the mixed system is 4.8 to 5.1; and the preferred dropping rate is 2 to 5 mL / min.

[0030] Furthermore, step S3 includes: first mixing the modified hollow ceramic material, modified mica, modified inorganic whisker material and the mixed system for the first time, and then mixing with the silane coupling agent and the silicate compound for the second time; preferably, stirring is performed during the first mixing and the second mixing, and preferably the first stirring speed is 500-1000 rpm, the time is 1-2h, and the second stirring speed is 120-150 rpm, and the time is 12-24h.

[0031] Furthermore, in step S4, the coating is performed by spraying, and the preferred spraying thickness is 0.3 to 0.4 mm.

[0032] Furthermore, the curing temperature is 35 to 45° C. and the curing time is 2 to 24 hours.

[0033] Another aspect of the present invention provides a thermal insulation coating, which is prepared using the preparation method of the thermal insulation coating provided in the present application.

[0034] Another aspect of the present invention provides a lithium-ion battery, comprising a battery cell and a battery cell shell, wherein at least one side surface of the battery cell shell is provided with the above-mentioned thermal insulation coating provided in the present application.

[0035] By applying the technical solution of the present invention, the introduction of the modified hollow ceramic material in the thermal insulation coating composition of the present application can give play to the advantage of its low thermal conductivity and improve the thermal insulation performance of the thermal insulation coating prepared therefrom; mica has a lamellar structure, and the introduction of modified mica can form a dense layer inside the thermal insulation coating to isolate the convection inside the coating, thereby improving the thermal insulation performance of the thermal insulation coating; the modified inorganic whisker material can form an interconducting structure inside the thermal insulation coating prepared therefrom, and play its mechanical reinforcement role, thereby improving the thermal insulation performance of the thermal insulation coating while improving its mechanical strength. Moreover, the surfaces of the above-mentioned modified hollow ceramic material, modified mica and modified inorganic whisker material all contain a large number of hydroxyl groups. Under the catalysis of an acidic catalyst, the hydrolysis products of alkaline silica sol, silane coupling agent and silicate compound are bonded to the hydroxyl groups on the surface of the above-mentioned material in component A, thereby improving the stability and mechanical strength of the cross-linked structure in the prepared thermal insulation coating, and at the same time, it can also improve its adhesion to the surface of the battery shell, thereby better exerting the thermal insulation performance. Moreover, even if the volume of the battery cell expands or contracts during use, the thermal insulation coating will not peel off or lose powder, thereby ensuring the normal use of the battery cell. In addition, the introduction of the above-mentioned component A can also improve the electrolyte corrosion resistance of the thermal insulation coating.

[0036] Applying the above-mentioned thermal insulation coating to the battery cell shell can improve the safety of the battery and the thermal runaway protection effect, delay the increase in the shell surface temperature when thermal runaway occurs inside the battery cell, and suppress the shell temperature below the metal softening point, thereby improving the impact strength of the shell, so that before the explosion-proof valve is opened, the shell will not melt under high temperature conditions and cause the shell to explode, and increase the probability of the explosion-proof valve opening before the shell ruptures, thereby improving the thermal safety performance of the battery module and battery pack when thermal runaway occurs in a single battery cell. DETAILED DESCRIPTION

[0037] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0038] As described in the background technology, the existing battery has the problem that the battery cell shell is prone to melting, burning and rupture after thermal runaway occurs. In order to solve the above technical problems, the first aspect of the present application provides a thermal insulation coating composition, which includes: component A and component B, component A includes modified hollow ceramic material, modified mica and modified inorganic whisker material; wherein the modified hollow ceramic material is a hydroxyl-modified hollow ceramic material, the modified mica is a hydroxyl-modified mica, and the modified inorganic whisker material is a hydroxyl-modified inorganic whisker material; component B includes an acidic catalyst, a solvent, an alkaline silica sol, a silane coupling agent and a silicate compound.

[0039] The introduction of the modified hollow ceramic material in the thermal insulation coating composition of the present application can give play to the advantage of its low thermal conductivity and improve the thermal insulation performance of the thermal insulation coating prepared therefrom; mica has a lamellar structure, and the introduction of modified mica can form a dense layer inside the thermal insulation coating to isolate the convection inside the coating, thereby improving the thermal insulation performance of the thermal insulation coating; the modified inorganic whisker material can form an interconducting structure inside the thermal insulation coating prepared therefrom, and play its mechanical reinforcement role, thereby improving the thermal insulation performance of the thermal insulation coating while improving its mechanical strength. Moreover, the surfaces of the above-mentioned modified hollow ceramic material, modified mica and modified inorganic whisker material all contain a large number of hydroxyl groups. Under the catalysis of an acidic catalyst, the hydrolysis products of alkaline silica sol, silane coupling agent and silicate compound are bonded to the hydroxyl groups on the surface of the above-mentioned materials in component A, thereby improving the stability and mechanical strength of the cross-linked structure in the prepared thermal insulation coating, and at the same time, it can also improve its adhesion to the surface of the battery cell shell, thereby better exerting the thermal insulation performance. Moreover, even if the volume of the battery cell expands or contracts during use, the thermal insulation coating will not peel off or lose powder, thereby ensuring the normal use of the battery cell. In addition, the introduction of the above-mentioned component A can also improve the electrolyte corrosion resistance of the thermal insulation coating.

[0040] Applying the above-mentioned thermal insulation coating to the battery cell shell can improve the safety of the battery and the thermal runaway protection effect, delay the increase in the shell surface temperature when thermal runaway occurs inside the battery cell, and suppress the shell temperature below the metal softening point, thereby improving the impact strength of the shell, so that before the explosion-proof valve is opened, the shell will not melt under high temperature conditions and cause the shell to explode, and increase the probability of the explosion-proof valve opening before the shell ruptures, thereby improving the thermal safety performance of the battery module and battery pack when thermal runaway occurs in a single battery cell.

[0041] In a preferred embodiment, by weight, component A includes 10 to 21 parts of modified hollow ceramic material, 5 to 10 parts of modified mica, and 5 to 10 parts of modified inorganic whisker material, and component B includes 0.1 to 3 parts of acid catalyst, 1 to 6 parts of solvent, 20 to 40 parts of alkaline silica sol, 20 to 40 parts of silane coupling agent and 5 to 10 parts of silicate compound. Compared with other ranges, limiting the amount of the above components in the thermal insulation coating composition to the above range is conducive to improving the thermal insulation performance and mechanical strength of the thermal insulation coating, and is conducive to inhibiting the melting of the shell and causing the shell to burn through and rupture, thereby improving the safety of the battery and the safety of the battery module and battery pack.

[0042] In order to further improve the thermal insulation performance and mechanical strength of the thermal insulation coating, and further inhibit the melting of the shell and the resulting burn-through and rupture of the shell, preferably, by weight, component A includes 15 to 21 parts of modified hollow ceramic material, 5 to 8 parts of modified mica, 5 to 8 parts of modified inorganic whisker material, and component B includes 1.2 to 1.6 parts of acidic catalyst, 1.5 to 2.5 parts of solvent, 25 to 35 parts of alkaline silica sol, 25 to 30 parts of silane coupling agent and 6 to 8 parts of silicate compound.

[0043] In a preferred embodiment, component A includes at least two hydroxyl-modified hollow ceramic materials with average particle sizes of 5 to 10 μm and 15 to 50 μm, respectively. By compounding the above two modified hollow ceramic materials with average particle sizes, it is beneficial to improve the packing density in three-dimensional space, thereby improving the compactness and mechanical strength of the thermal insulation coating, and also helping to improve its resistance to electrolyte corrosion.

[0044] In order to further improve the density, mechanical strength and electrolyte corrosion resistance of the thermal insulation coating, preferably, the amount of hollow ceramic material with an average particle size of 15 to 50 μm is greater than the amount of hollow ceramic material with an average particle size of 5 to 10 μm; more preferably, the weight ratio of the two is (2 to 3):1.

[0045] In a preferred embodiment, the average particle size of the mica is 10 to 15 μm. The average particle size of the mica includes but is not limited to the above range, and limiting it within the above range is conducive to better forming a dense layer inside the thermal insulation coating, which is conducive to reducing convection inside the insulation coating, thereby facilitating improving the thermal insulation performance of the thermal insulation coating.

[0046] In a preferred embodiment, the mica includes but is not limited to one or more of the group consisting of phlogopite, sericite and fluorophlogopite. Compared with other types, the use of the above types of mica is conducive to further improving the thermal insulation performance of the thermal insulation coating.

[0047] In a preferred embodiment, the inorganic whisker material includes but is not limited to potassium titanate whiskers and / or calcium sulfate whiskers. Compared with other types, the use of the above-mentioned types of inorganic whisker materials is conducive to the formation of an interconducting structure inside the thermal insulation coating, which is conducive to better exerting its mechanical reinforcement effect, thereby helping to improve the thermal insulation performance and mechanical strength of the thermal insulation coating. Moreover, potassium titanate whiskers themselves have excellent radiation resistance and low cost, and can reflect infrared light into the interior of the battery cell without being absorbed by the shell, thereby further improving the thermal insulation performance of the thermal insulation coating.

[0048] In order to further improve the thermal insulation performance and mechanical strength of the thermal insulation coating, preferably, the aspect ratio of the potassium titanate whisker is (10-15):1; the aspect ratio of the calcium sulfate whisker is (10-15):1.

[0049] In a preferred embodiment, the inorganic whisker material is a combination of potassium titanate whiskers and calcium sulfate whiskers, and the weight ratio of the two is (1-2): 1. The use of the above two specific types and amounts of inorganic whisker materials is beneficial to further improve the thermal insulation performance and mechanical strength of the thermal insulation coating.

[0050] In a preferred embodiment, the acidic catalyst includes but is not limited to p-toluenesulfonic acid, hydrochloric acid and glacial acetic acid. The use of a single acidic catalyst to regulate the pH value is prone to large fluctuations, and the control of the pH value has a great influence on the strength of the coating. Compared with the use of a single type of acidic catalyst, the present application can effectively reduce the volatility of the pH value by compounding multiple acid sources, which is conducive to improving the stability of the quality of the thermal insulation coating.

[0051] In order to further improve the quality stability of the thermal insulation coating, preferably, the weight ratio of p-toluenesulfonic acid, hydrochloric acid and glacial acetic acid is (0.1-0.5):(0.1-0.5):(0.5-1.5), and the mass concentration of hydrochloric acid is preferably 3.65-7.3 g / L.

[0052] In order to improve the dispersibility and compatibility of the acidic catalyst in the solvent, preferably, the solvent includes but is not limited to one or more of the group consisting of isopropanol, acetone and water.

[0053] In a preferred embodiment, the solid content of the alkaline silica sol is 10 to 35 wt %. The solid content of the alkaline silica sol includes but is not limited to the above range, and limiting it within the above range is conducive to improving the bonding force between the alkaline silica sol and the modified hollow ceramic material, modified mica and modified inorganic whisker material in component A, and is conducive to improving the viscosity of the thermal insulation coating, inhibiting the agglomeration of the silica sol particles, and thus is conducive to improving the processing performance (such as spraying construction performance) of the thermal insulation coating.

[0054] In a preferred embodiment, the silane coupling agent includes but is not limited to one or more of the group consisting of methyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane and triethoxyvinylsilane. Compared with other types, the use of the above-mentioned types of silane coupling agents is conducive to generating hydrolysis products at a more stable rate after compounding with silicate compounds, thereby further improving the compactness and solvent resistance of the thermal insulation coating; at the same time, it is also conducive to improving the adhesion and mechanical strength of the thermal insulation coating.

[0055] In a preferred embodiment, the silicate compounds include but are not limited to ethyl orthosilicate. Compared with other types, the use of the above-mentioned silicate compounds is conducive to generating hydrolysis products at a more stable rate after compounding with the silane coupling agent, thereby further improving the compactness and solvent resistance of the thermal insulation coating; at the same time, it is also conducive to further improving the adhesion and mechanical strength of the thermal insulation coating.

[0056] In order to further improve the thermal insulation performance, adhesion and mechanical strength of the thermal insulation coating, in a preferred embodiment, the weight ratio of component A to component B is (25-35):(65-75).

[0057] In order to further improve the thermal insulation performance, adhesion and mechanical strength of the thermal insulation coating, preferably, the weight ratio of component A to component B is (30-32):(67-70).

[0058] The second aspect of the present application provides a method for preparing a thermal insulation coating, which comprises: step S1, hydroxylating and modifying a hollow ceramic material, mica and an inorganic whisker material to obtain a modified hollow ceramic material, a modified mica and a modified inorganic whisker material; step S2, mixing an acidic catalyst, a solvent and an alkaline silica sol to obtain a mixed system; step S3, mixing the modified hollow ceramic material, the modified mica, the modified inorganic whisker material and the mixed system with a silane coupling agent and a silicate compound to obtain a thermal insulation coating; step S4, coating the thermal insulation coating on the surface of a battery cell shell, and obtaining a shell containing a thermal insulation coating after curing; the modified hollow ceramic material, the modified mica, the modified inorganic whisker material, the acidic catalyst, the solvent, the alkaline silica sol, the silane coupling agent and the silicate compound have the same definitions as in the previous text.

[0059] In step S1, the hollow ceramic material, mica and inorganic whisker material are hydroxylated and modified so that a large number of hydroxyl groups are contained on their surface. If the pH of the mixed system prepared in step S2 is too low, it will lead to too fast ripening, thereby reducing the use time, and if the pH is too high, the risk of gelation will be significantly increased. In step S3, the above raw materials are mixed, and in this process, the alkaline silica sol, silane coupling agent and silicate compound undergo hydrolysis reaction to obtain a hydrolysis product, which is bonded to the hydroxyl groups on the surface of the modified hollow ceramic material, modified mica and modified inorganic whisker material to obtain a thermal insulation coating. In step S4, the thermal insulation coating is applied to the surface of the battery cell shell, and a shell containing a thermal insulation coating is obtained after curing.

[0060] The present application introduces the modified hollow ceramic material in the preparation method of the above-mentioned thermal insulation coating to give play to its advantage of low thermal conductivity and improve the thermal insulation performance of the thermal insulation coating prepared therefrom; mica has a lamellar structure, and the introduction of modified mica can form a dense layer inside the thermal insulation coating to isolate the convection inside the coating, thereby improving the thermal insulation performance of the thermal insulation coating; the modified inorganic whisker material can form an interconducting structure inside the thermal insulation coating prepared therefrom, and play its mechanical reinforcement role, thereby improving the thermal insulation performance of the thermal insulation coating while improving its mechanical strength. Moreover, the surfaces of the above-mentioned modified hollow ceramic material, modified mica and modified inorganic whisker material all contain a large number of hydroxyl groups. Under the catalysis of an acidic catalyst, the hydrolysis products of alkaline silica sol, silane coupling agent and silicate compound are bonded to the hydroxyl groups on the surface of the above-mentioned material in component A, thereby improving the stability and mechanical strength of the cross-linked structure in the prepared thermal insulation coating, and at the same time, it can also improve its adhesion to the surface of the battery cell shell, thereby better exerting the thermal insulation performance.

[0061] Applying the above-mentioned thermal insulation coating to the battery cell shell can improve the safety of the battery and the thermal runaway protection effect, delay the increase in the shell surface temperature when thermal runaway occurs inside the battery cell, and suppress the shell temperature below the metal softening point, thereby improving the impact strength of the shell, so that before the explosion-proof valve is opened, the shell will not melt under high temperature conditions and cause the shell to explode, and increase the probability of the explosion-proof valve opening before the shell ruptures, thereby improving the thermal safety performance of the battery module and battery pack when thermal runaway occurs in a single battery cell.

[0062] In a preferred embodiment, step S1 includes: mixing hollow ceramic material, mica and inorganic whisker material with hydrogen peroxide and reacting to obtain a product system containing a modified product; mixing the modified product with water to obtain an aqueous dispersion of the modified product, and spray drying the aqueous dispersion to obtain a modified hollow ceramic material, modified mica, and modified inorganic whisker material. Compared with other modification methods, the hydroxylation modification of hollow ceramic material, mica and inorganic whisker material using the above process can obtain a material containing a large number of hydroxyl groups on the surface, which is convenient for subsequent bonding with the hydrolysis product, thereby facilitating the improvement of the stability and mechanical strength of the cross-linked structure in the obtained thermal insulation coating; moreover, the above spray drying operation is simple.

[0063] In order to improve the dispersibility and compatibility of the hollow ceramic material, mica and inorganic whisker material with hydrogen peroxide, preferably, the mixing and reaction in step S1 are carried out under stirring conditions, preferably with a stirring rate of 200 to 500 rpm and a stirring temperature of 80 to 120°C.

[0064] In order to improve the effect of hydroxyl modification of each raw material, and at the same time to improve the processing efficiency and raw material utilization, preferably, the ratio of the sum of the weight of the hollow ceramic material, mica and inorganic whisker material to the volume of hydrogen peroxide is (20-40) g: (20-50) L; preferably, the mass concentration of hydrogen peroxide in hydrogen peroxide is 300-500 g / L.

[0065] In order to further improve the hydroxylation modification effect, preferably, the spray drying temperature is 100-110° C., the time is 0.5-2 h, and the pressure is 0.6-1.0 MPa.

[0066] In a preferred embodiment, step S2 includes: mixing an acidic catalyst with a solvent to obtain an acidic catalyst dispersion, and adding the acidic catalyst dispersion dropwise to an alkaline silica sol under stirring to obtain a mixed system, wherein the pH of the mixed system is 4.8 to 5.1. If the acidic catalyst is poured into the alkaline silica sol at one time to mix the two, the local pH of the system will be low, causing the alcohol sol to be locally excessively cross-linked and cured, which will affect the comprehensive performance of the thermal insulation coating. The above-mentioned dropping method of the present application is conducive to more accurate control of the pH value of the system, reducing the occurrence of local excessive cross-linking and curing, and thus helping to improve the comprehensive performance of the thermal insulation coating. Compared with other ranges, limiting the pH of the mixed system within the above range can improve its processability and better meet the needs of large-scale production.

[0067] In order to more accurately control the pH value of the system and reduce the occurrence of local excessive cross-linking and curing, the preferred droplet acceleration rate is 2 to 5 mL / min.

[0068] In a preferred embodiment, step S3 includes: firstly mixing the modified hollow ceramic material, the modified mica, the modified inorganic whisker material with the mixed system for the first time, and then mixing with the silane coupling agent and the silicate compound for the second time. The above steps are used for mixing, which is beneficial to pre-mixing the modified hollow ceramic material, the modified mica, and the modified inorganic whisker material to improve their dispersibility, and then mixing with the silane coupling agent and the silicate compound for the second time, so that a hydrolysis reaction is carried out in the process, which is beneficial to improve the efficiency of the hydrolysis reaction.

[0069] In order to further improve the dispersibility of each raw material, preferably, stirring is performed during the first mixing and the second mixing, preferably the first stirring speed is 500-1000 rpm, the time is 1-2 hours, and the second stirring speed is 120-150 rpm, the time is 12-24 hours.

[0070] In a preferred embodiment, the coating in step S4 is performed by spraying. Compared with other methods, spraying is convenient for improving the thickness uniformity of the thermal insulation coating, thereby facilitating better exertion of the thermal insulation effect of the thermal insulation coating.

[0071] In order to further enhance the heat insulation effect of the heat insulation coating, preferably, the spraying thickness is 0.3 to 0.4 mm.

[0072] In a preferred embodiment, the curing temperature is 35-45°C and the curing time is 2-24 hours. The curing temperature and time include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the curing effect, thereby improving the mechanical strength, thermal insulation performance and other comprehensive properties of the thermal insulation coating.

[0073] The third aspect of the present application also provides a thermal insulation coating, which is prepared by the preparation method of the thermal insulation coating provided in the present application. The thermal insulation coating prepared by the preparation method of the thermal insulation coating has excellent thermal insulation properties, mechanical properties, adhesion and electrolyte resistance. The application of the thermal insulation coating in the battery cell shell can improve the safety of the battery and the thermal runaway protection effect, delay the increase in the surface temperature of the shell when thermal runaway occurs inside the battery cell, and suppress the shell temperature below the metal softening point, thereby improving the impact strength of the shell, so that before the explosion-proof valve is opened, the shell does not melt under high temperature conditions, causing the shell to explode, and increase the probability of the explosion-proof valve opening before the shell ruptures, thereby improving the thermal safety performance of the battery module and battery pack in the case of thermal runaway of a single battery cell.

[0074] The fourth aspect of the present application also provides a lithium-ion battery, including a battery cell and a battery cell shell, at least one side surface of the battery cell shell is provided with the above-mentioned thermal insulation coating provided in the present application. The above-mentioned thermal insulation coating provided in the present application has excellent thermal insulation performance, mechanical properties, adhesion and electrolyte resistance. Providing the above-mentioned thermal insulation coating on the surface of the battery cell shell can improve the safety and thermal runaway protection effect of the battery, delay the increase in the surface temperature of the shell when thermal runaway occurs inside the battery cell, and suppress the shell temperature below the metal softening point, thereby improving the impact strength of the shell, so that before the explosion-proof valve is opened, the shell does not melt under high temperature conditions, resulting in the shell bursting problem, and the probability of the explosion-proof valve opening before the shell ruptures is increased, thereby improving the thermal safety performance of the battery module and battery pack in the case of thermal runaway of a single battery cell.

[0075] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0076] Example 1

[0077] A method for preparing a thermal insulation coating, comprising:

[0078] (1) According to a weight ratio of 12.1:4.8:7.3:4.8:2.4, a hollow ceramic material with an average particle size of 20 μm, a hollow ceramic material with an average particle size of 5 μm, mica with an average particle size of 12 μm, potassium titanate whiskers with an aspect ratio of 15:1 (D50 is 12 μm), and calcium sulfate whiskers with an aspect ratio of 15:1 (D50 is 5 μm) are weighed in sequence, and the above five materials are mixed with a mass concentration of 300 g / L hydrogen peroxide and reacted, and stirred at 300 rpm for 4 h at 100° C. After the stirring is completed, the mixture is cooled to room temperature, filtered to obtain a solid phase product, and washed with water to obtain a modified product, the modified product is mixed with water to obtain an aqueous dispersion of the modified product, and the aqueous dispersion of the modified product is spray-dried to obtain a modified hollow ceramic material, a modified mica, and a modified inorganic whisker material, wherein the spray drying temperature is 110° C., the time is 0.5 h, and the pressure is 1.0 MPa;

[0079] (2) 8 g of p-toluenesulfonic acid was mixed with 52.5 g of isopropanol to completely dissolve the p-toluenesulfonic acid, and the resulting solution was set aside; 3.5 g of concentrated hydrochloric acid with a mass concentration of 73 g / L, 30 g of glacial acetic acid and 6 g of water were mixed with the above-mentioned standby solution to obtain an acidic catalyst dispersion, and the above-mentioned acidic catalyst dispersion was added dropwise to 300 mL of alkaline silica sol (mass concentration of 30 wt%) at a rate of 3 mL / min under stirring at 300 rpm. With the addition of the acidic catalyst dispersion, the pH gradually decreased until the pH was 4.8 to 5.1, and the addition was stopped to obtain a mixed system. The entire addition process was controlled within 5 min;

[0080] (3) The modified hollow ceramic material, modified mica, modified inorganic whisker material and the mixed system prepared in step (2) are mixed for the first time at 500 rpm, stirred for 2 h, and then 280 g of methyltrimethoxysilane and 70 g of ethyl orthosilicate are added for the second mixing, and the stirring is maintained at a speed of 120 rpm. After 16 h, the stirring is stopped to obtain a thermal insulation coating; it should be noted that the pH of the system is maintained in the range of 4.8 to 5.1 during the stirring process;

[0081] (4) The battery cell shell (model 60150253) was sandblasted to increase the roughness of the shell surface and release the stress in the shell molding process; the shell surface after sandblasting was sprayed with a spraying method, with a spraying thickness of 0.3 mm, and the shell after spraying was dried at 45°C for 4 hours, and then placed at room temperature for 48 hours to allow the thermal insulation coating to completely solidify, and then cleaned in an ultrasonic cleaner, and then the inside of the shell was sprayed with deionized water, and finally dried at 80°C to obtain a shell containing a thermal insulation coating. The thickness of the thermal insulation coating is 0.3 mm.

[0082] Example 2

[0083] The difference from Example 1 is that an equal amount of hollow ceramic material with an average particle size of 20 μm is used to replace the hollow ceramic material with an average particle size of 5 μm in step (1), that is, the average particle size of the hollow ceramic material in component A is 20 μm.

[0084] Example 3

[0085] The difference from Example 1 is that in step (1), the weight ratio of the hollow ceramic material with an average particle size of 20 μm to the hollow ceramic material with an average particle size of 5 μm is 1:1.

[0086] Example 4

[0087] The difference from Example 1 is that in step (1), the weight ratio of the hollow ceramic material with an average particle size of 20 μm to the hollow ceramic material with an average particle size of 5 μm is 2:1.

[0088] Example 5

[0089] The difference from Example 1 is that in step (1), the weight ratio of the hollow ceramic material with an average particle size of 20 μm to the hollow ceramic material with an average particle size of 5 μm is 3:1.

[0090] Example 6

[0091] The difference from Example 1 is that in step (1), the weight ratio of the hollow ceramic material with an average particle size of 20 μm to the hollow ceramic material with an average particle size of 5 μm is 5:1.

[0092] Example 7

[0093] The difference from Example 1 is that in step (1), an equal amount of calcium sulfate whiskers (having the same aspect ratio as in Example 1) are used to replace potassium sulfate whiskers, i.e., potassium sulfate whiskers are not introduced into component A.

[0094] Example 8

[0095] The difference from Example 1 is that the amounts of the modified hollow ceramic material, the modified mica and the modified inorganic whisker material in component A are changed, and the weight ratio of the three is 20:5:5.

[0096] Comparative Example 1

[0097] The difference from Example 1 is that step (1) is omitted, and in step (3), the modified hollow ceramic material, modified mica, modified inorganic whisker material and the mixed system obtained in step (2) are not mixed, and methyltrimethoxysilane and tetraethyl orthosilicate are directly added for the second mixing and subsequent steps. The components and amounts of the thermal insulation coating composition are shown in Table 1.

[0098] Comparative Example 2

[0099] The difference from Example 1 is that the hollow ceramic material, mica, potassium titanate whisker and calcium sulfate whisker are not hydroxylated, and the unmodified materials are directly used for subsequent steps (2) to (4). The components and amounts of the thermal insulation coating composition are shown in Table 1.

[0100] Comparative Example 3

[0101] The difference from Example 1 is that potassium titanate whiskers and calcium sulfate whiskers are not introduced in step (1), only hollow ceramic materials of the above two particle sizes and mica are used for hydroxylation modification, and subsequent steps (2) to (4) are carried out. The components and amounts of the thermal insulation coating composition are shown in Table 1.

[0102] The components and amounts of the thermal insulation coating compositions in Example 1 and Comparative Examples 1 to 3 are shown in Table 1.

[0103] Table 1

[0104]

[0105] The components and amounts of the thermal insulation coating compositions in Examples 2 to 6 are shown in Table 2.

[0106] Table 2

[0107]

[0108] The components and amounts of the thermal insulation coating compositions in Examples 7 to 10 are shown in Table 3.

[0109] Table 3

[0110]

[0111] The thermal insulation coatings prepared in all the above embodiments and comparative examples were made into coatings according to corresponding standards and subjected to electrolyte resistance test, thermal insulation temperature rise test, adhesion test, high and low temperature impact test. The test results are shown in Table 4.

[0112] Table 4

[0113]

[0114] The above-mentioned shell containing the heat insulation coating was assembled into a lithium-ion battery, the positive electrode was a ternary positive electrode material NCM, the capacity was 160Ah, the rated voltage was 4.2V, and the SOC (state of charge or the remaining available power in the battery cell) was 100%. The assembled lithium-ion battery was subjected to a single-cell thermal runaway test, and the test items and test results are shown in Table 5.

[0115] Table 5

[0116]

[0117] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0118] It can be seen from the test results of Example 1 and Comparative Example 1 that the thermal insulation coating without adding any powder itself has good resistance to electrolyte corrosion. The reason is that the structure of the thermal insulation coating after curing is mainly silicon-oxygen bonds, the film is dense, and it has good resistance to solvent corrosion. However, Comparative Example 1 does not add any thermal insulation material, so the back surface temperature is the highest in the thermal insulation temperature rise test, which is 588°C, much higher than 406°C in Example 1. Therefore, in the single-cell thermal runaway test, the gas production rate is too fast after the cell triggers thermal runaway, the internal pressure of the cell shell rises rapidly, and the temperature is too high, causing the shell temperature to quickly reach the softening point of the shell material, thereby losing strength. Under the gas production pressure, the shell ruptures before the explosion-proof valve.

[0119] It can be seen from the test results of Example 1 and Comparative Example 2 that although the formula compositions of the two are exactly the same, because the hollow ceramic material, mica, potassium titanate whiskers and calcium sulfate whiskers in Comparative Example 2 are not surface hydroxylated, the powder has poor compatibility with the thermal insulation coating itself, cannot form a chemical link with the film-forming substance, and the film density is also reduced. Under the action of the electrolyte, the solution penetrates into the interior of the thermal insulation coating. Therefore, the adhesion after electrolyte immersion is significantly reduced, and the thermal insulation performance is also reduced to a certain extent; in the single-cell thermal runaway test, the maximum temperature of the shell can be further reduced, but it is not as good as Example 1, because the bonding ability of the powder and the film-forming substance is poor, resulting in partial detachment of the coating from the shell.

[0120] It can be seen from the test results of Example 1 and Comparative Example 3 that both have good resistance to electrolyte corrosion, and the single-cell thermal runaway test results are also relatively close. However, since Comparative Example 3 does not introduce high aspect ratio potassium titanate whiskers and calcium sulfate whiskers, under the high temperature and high pressure of thermal runaway of the battery cell, some cracks are generated in the coating on the shell, and the maximum temperature of the shell surface is also somewhat higher than that of Example 1.

[0121] From the test results of Example 1 and Example 2, it can be seen that Example 2 only adds a single 20 μm large-particle hollow ceramic microbead, and the addition amount is large, resulting in a decrease in the coating performance of the film-forming material on the filler, so the adhesion level after electrolyte immersion is level 1, slightly lower than Example 1; at the same time, in Example 2, because the volume accumulation gaps of the large-particle hollow ceramic microbeads are filled with film-forming resins and other powders (mica powder, potassium titanate and calcium sulfate whiskers), the thermal conductivity of these powders is higher than that of 5 μm hollow ceramic microbeads, so the thermal insulation performance of Example 2 is not as good as that of Example 1, and the temperature in the thermal insulation temperature rise test and the single-cell test is higher than that of Example 1, but better than that of Comparative Example 1. Similarly, the test results of Example 3 are between Example 1 and Example 2.

[0122] In Examples 4 to 6, the total amount of hollow ceramic material remains unchanged. As the proportion of large-particle hollow ceramic material increases, the volume ratio it occupies in the thermal insulation coating becomes higher, the film-forming strength decreases, and after reaching a certain limit, the bonding strength with the shell decreases. In the thermal runaway test of the battery cell, the coating and the shell are prone to fall off or peel off, resulting in a deterioration in the thermal insulation effect.

[0123] The difference between Example 7 and Example 1 is that the high aspect ratio whiskers in Example 7 only include calcium sulfate whiskers. The infrared reflectivity of the calcium sulfate whiskers themselves is lower than that of the potassium titanate whiskers. When a single battery cell has thermal runaway, the temperature is high and the proportion of infrared radiation heat transfer is large. Therefore, the thermal insulation effect of Example 7 is much lower than that of Example 1, but better than that of Comparative Example 1.

[0124] In Example 8, the addition amount of component A is consistent with that in Example 1, but the weight ratio of the hollow thermal insulation filler, mica powder and high aspect ratio inorganic whisker material in Example 8 is 20:5:5, while the ratio of the three in Example 1 is about 2.3:1:1. Because the proportion of hollow ceramic material in Example 8 is too high, the high aspect ratio inorganic whisker material and mica cannot form a good bridging effect between the systems, and are prone to cracking and falling off under high temperature impact. Therefore, the thermal insulation effect is the worst among Examples 1 to 8, but slightly better than the comparative example.

[0125] By spraying the above-mentioned thermal insulation coating provided in this application on the inside of the battery cell shell to obtain a thermal insulation coating, the shell strength of the battery cell under high temperature and high pressure in the face of thermal runaway can be effectively improved, and the shell explosion problem caused by the reduction of metal strength of the battery cell shell due to high temperature can be solved. The heat inside the battery cell can be orderly and directed out from the explosion-proof valve, thereby significantly improving the safety of the battery pack.

[0126] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0127] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A thermal insulation coating composition, characterized in that: The thermal insulation coating composition comprises: A component, wherein the A component comprises a modified hollow ceramic material, modified mica and a modified inorganic whisker material; wherein the modified hollow ceramic material is a hydroxyl-modified hollow ceramic material, the modified mica is a hydroxyl-modified mica, and the modified inorganic whisker material is a hydroxyl-modified inorganic whisker material; The B component comprises an acidic catalyst, a solvent, an alkaline silica sol, a silane coupling agent and a silicate compound.

2. The thermal insulation coating composition according to claim 1, characterized in that: In parts by weight, the component A includes 10 to 21 parts of the modified hollow ceramic material, 5 to 10 parts of the modified mica, and 5 to 10 parts of the modified inorganic whisker material; the component B includes 0.1 to 3 parts of the acid catalyst, 1 to 6 parts of the solvent, 20 to 40 parts of the alkaline silica sol, 20 to 40 parts of the silane coupling agent, and 5 to 10 parts of the silicate compound; Preferably, the weight ratio of the component A to the component B is (25-35):(65-75).

3. The thermal insulation coating composition according to claim 1 or 2, characterized in that: The A component includes at least two hydroxyl-modified hollow ceramic materials having average particle sizes of 5 to 10 μm and 15 to 50 μm respectively; Preferably, the amount of the hollow ceramic material with an average particle size of 15 to 50 μm is greater than the amount of the hollow ceramic material with an average particle size of 5 to 10 μm; more preferably, the weight ratio of the two is (2 to 3):

1.

4. The thermal insulation coating composition according to claim 1 or 2, characterized in that: The average particle size of the mica is 10 to 15 μm; Preferably, the mica is selected from one or more of the group consisting of phlogopite, sericite and fluorophlogopite.

5. The thermal insulation coating composition according to any one of claims 1 to 4, characterized in that: The inorganic whisker material is selected from potassium titanate whiskers and / or calcium sulfate whiskers; Preferably, the aspect ratio of the potassium titanate whisker is (10-15):1; Preferably, the aspect ratio of the calcium sulfate whisker is (10-15):1; Preferably, the inorganic whisker material is a combination of potassium titanate whiskers and calcium sulfate whiskers, and the weight ratio of the two is (1-2):

1.

6. The thermal insulation coating composition according to claim 5, characterized in that: The acid catalyst is selected from p-toluenesulfonic acid, hydrochloric acid and glacial acetic acid; preferably, the weight ratio of p-toluenesulfonic acid, hydrochloric acid and glacial acetic acid is (0.1-0.5):(0.1-0.5):(0.5-1.5); preferably, the mass concentration of hydrochloric acid is 3.65-7.3 g / L; Preferably, the solvent is selected from one or more of the group consisting of isopropanol, acetone and water; Preferably, the solid content of the alkaline silica sol is 10 to 35 wt %; Preferably, the silane coupling agent is selected from one or more of the group consisting of methyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane and triethoxyvinylsilane; Preferably, the silicate compound is selected from tetraethyl orthosilicate.

7. A method for preparing a thermal insulation coating, characterized in that: The preparation method comprises: Step S1, hydroxylating and modifying the hollow ceramic material, mica and inorganic whisker material to obtain modified hollow ceramic material, modified mica and modified inorganic whisker material; Step S2, mixing an acidic catalyst, a solvent and an alkaline silica sol to obtain a mixed system; Step S3, mixing the modified hollow ceramic material, the modified mica, the modified inorganic whisker material, the mixed system, the silane coupling agent and the silicate compound to obtain a thermal insulation coating; Step S4, coating the thermal insulation coating on the surface of the battery cell shell, and obtaining a shell containing the thermal insulation coating after curing; The modified hollow ceramic material, the modified mica, the modified inorganic whisker material, the acid catalyst, the solvent, the alkaline silica sol, the silane coupling agent and the silicate compound have the same definitions as in claim 1, respectively.

8. The method for preparing the thermal insulation coating according to claim 7, characterized in that: The step S1 comprises: mixing the hollow ceramic material, the mica and the inorganic whisker material with hydrogen peroxide and reacting them to obtain a product system containing a modified product; mixing the modified product with water to obtain an aqueous dispersion of the modified product, and spray-drying the aqueous dispersion to obtain the modified hollow ceramic material, the modified mica and the modified inorganic whisker material; the mixing and reacting processes are preferably carried out under stirring conditions, preferably with a stirring rate of 200 to 500 rpm and a stirring temperature of 80 to 120° C.; Preferably, the ratio of the sum of the weights of the hollow ceramic material, the mica and the inorganic whisker material to the volume of the hydrogen peroxide is (20-40) g: (20-50) L; preferably, the mass concentration of hydrogen peroxide in the hydrogen peroxide is 300-500 g / L; Preferably, the spray drying temperature is 100-110°C, the time is 0.5-2h, and the pressure is 0.6-1.0MPa; Preferably, the step S2 comprises: mixing the acidic catalyst with the solvent to obtain an acidic catalyst dispersion, and dropping the acidic catalyst dispersion into the alkaline silica sol under stirring conditions to obtain the mixed system, wherein the pH of the mixed system is 4.8 to 5.1; preferably, the dropping rate is 2 to 5 mL / min; Preferably, the step S3 comprises: firstly mixing the modified hollow ceramic material, the modified mica, the modified inorganic whisker material and the mixed system for the first time, and then mixing with the silane coupling agent and the silicate compound for the second time; preferably, stirring is performed during the first mixing and the second mixing, and preferably the first stirring speed is 500-1000 rpm, the time is 1-2 hours, and the second stirring speed is 120-150 rpm, and the time is 12-24 hours; Preferably, the coating in step S4 is performed by spraying, and preferably the spraying thickness is 0.3-0.4 mm; Preferably, the curing temperature is 35-45° C. and the curing time is 2-24 hours.

9. A thermal insulation coating, characterized in that: The thermal insulation coating is prepared by the preparation method of the thermal insulation coating according to claim 7 or 8.

10. A lithium ion battery, comprising a battery cell and a battery cell shell, characterized in that: At least one side surface of the battery cell shell is provided with the thermal insulation coating according to claim 9.